Cortical activity during painful and non-painful stimulation over four lower limb body sites: a functional near-infrared spectroscopy study - Liao, Jiawen; Silvoni, Stefano; Desch, Simon; Serian, Angela; Andoh, Jamila; Flor, Herta (Scientific reports, 2025)
Functional near-infrared spectroscopy (fNIRS) holds potential utility as a measure of neural correlates of pain. However, most studies have focused on upper limb stimulation, with limited investigation into lower limbs. In this study, we utilized fNIRS to observe brain changes in oxyhemoglobin levels during painful and non-painful electrical stimulation of various lower limb sites (bilateral groins and knees) in 16 healthy participants. Additionally, we explored perceptual responses to painful and non-painful electrical stimulation across these lower limb sites. Our findings showed no significant main effect of stimulation across different body sites on oxyhemoglobin activity. However, the interaction between body sites, stimulation modalities, and brain regions significantly influenced oxyhemoglobin activity. Specifically, we found a decrease of neuro-metabolic activity in prefrontal and bilateral primary somatosensory cortices during painful stimulation of the left groin compared to non-painful stimulation, whereas an increase of neuro-metabolic activity was observed during painful stimulation of the right knee. Our findings also revealed that stimulation intensity was notably lower for bilateral knees compared to the left groin. These findings underscore the potential and feasibility of utilizing fNIRS to investigate pain mechanisms related to stimulation across distinct lower limb regions.